Retrieval of Embolized Amplatzer Patent Foramen Ovale Occlusion Device: Issues Related to Late Recognition - Allan J. Davies; Nicholas Collins; Nicole Organ (Case Reports in Cardiology)
Embolization of a percutaneous patent foramen ovale (PFO) closure device is a rare but serious complication. While early, periprocedural device embolization can normally be managed with snare and percutaneous retrieval, late embolization requires a different management strategy due to inability of the device to deform to allow passage into a large caliber sheath. We present a case of asymptomatic device embolization recognized six months following implantation and discuss the challenges encountered in successfully retrieving the device.